Kemajuan Bioteknologi dalam Diagnosis Tuberkulosis: Perkembangan Global dan Penerapannya di Indonesia - Aprillia, Cantika; Zahra , Aliya Azkia; Malau , Jekmal; Ainaputri , Aliza Salsabila; Siboro , Dewi Pratiwi Purba; Apriyanti , Endeh; Nugraha , Afif Tri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Tuberculosis (TB) remains a major global health burden, and Indonesia is among the countries with the highest incidence and mortality rates. Early and accurate diagnosis is essential for effective TB control; however, conventional diagnostic methods such as sputum smear microscopy, culture, chest radiography, and the tuberculin skin test continue to face limitations in sensitivity, specificity, turnaround time, and operational feasibility. This narrative review synthesizes global biotechnological developments in TB diagnostics and evaluates their potential applicability within the Indonesian healthcare system. A structured literature search was conducted using PubMed, ScienceDirect, and Google Scholar, applying Population, Intervention, Comparison, and Outcome (PICO) based inclusion and exclusion criteria. Key advances in molecular diagnostics include conventional polymerase chain reaction (PCR), real-time PCR, automated nucleic acid amplification test (NAAT) platforms such as GeneXpert, Xpert Ultra, and Truenat, as well as loop-mediated isothermal amplification (LAMP). Emerging innovations including CRISPR-based assays, biosensor platforms, microfluidic lab-on-chip devices, and nanotechnology-enhanced systems demonstrate improved sensitivity, portability, and testing speed, with potential for point-of-care implementation, although many require further field-based validation. No single diagnostic tool is universally optimal, as suitability depends on infrastructure availability, workforce capacity, and population needs. In Indonesia, persistent challenges include limited laboratory networks, high diagnostic costs, supply-chain constraints, and variability in human resource competence. Strengthening diagnostic systems, expanding decentralized testing, integrating digital health technologies, and supporting local production of diagnostic materials are critical to enable sustainable adoption and accelerate progress toward national TB elimination targets.